Firearm fatalities examined at Salt River medico-legal laboratory in 1999 and their investigative outcome by 2004 - Liebenberg, Linda (Department of Pathology, 2024)
The Republic of South Africa has OIle of the most liberal and human rights based constitutions wor1dWlde, with a very idealistic vision of individual freedom, alleviation of poverty access to education and health care and safety Many of the ideals are In direct redress of the previous regime, where only select strata of the populace had easy access to what are now constitutional rights for all.